Edukasi dan Skrining Pentingnya Pemantauan Obesitas Terhadap Terjadinya Resistensi Insulin Pada Lanjut Usia - Triyana Sari; Gracienne Gracienne; Ribka Anggeline Hariesti; Edwin Destra; Farell Christian Gunaidi; Yohanes Firmansyah (PPNI UNIMMAN, 2024)
Obesity is a condition where a person has an exceeds body weight than normal limit due to accumulation of excess fat in the body. Obesity closely related to insulin resistance, which is a condition where the body cannot respond to insulin effectively. Therefore, education and routine screening for the elderly in order to detect and manage insulin resistance at an early stage is very important. This service activity is carried out using the PDCA (Plan-Do-Check-Act) method, which includes education about healthy eating patterns, physical activity and weight management, as well as screening insulin levels. Based on these activities, education and screening have proven important in preventing further complications and improving the quality of life of the elderly.